2010
DOI: 10.1002/gps.2586
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a nursing guideline on depression in psychogeriatric nursing home residents with dementia

Abstract: This study shows significant reductions in depression severity by introducing a nursing guideline on psychogeriatric nursing home wards. Better compliance with the guideline could probably enlarge the effects. Some ways to achieve enhanced compliance are: (1) additionally train non-certified nurse assistants, and (2) emphasize necessary conditions for successful introduction of the guideline to nursing team managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Second, they may not yet fully recognize the benefits of engaging residents with advanced dementia in activities for their quality of life, despite the positive effects reported in several studies (e.g. Brooker, Wooley, & Lee, 2007;Schreiner, Yamamoto, & Shiotani, 2005;Verkaik et al, 2011;Volicer, Simard, Pupa, Medrek, & Riordan, 2006). Engaging residents in activities might seem of less value for the wellbeing of residents, than the basic physical care, a clean environment and comfort (Clare et al, 2008;Edvardsson et al, 2013) À also the things by which the staff are often judged upon by family caregivers, colleagues and care facility.…”
Section: Introductionmentioning
confidence: 91%
“…Second, they may not yet fully recognize the benefits of engaging residents with advanced dementia in activities for their quality of life, despite the positive effects reported in several studies (e.g. Brooker, Wooley, & Lee, 2007;Schreiner, Yamamoto, & Shiotani, 2005;Verkaik et al, 2011;Volicer, Simard, Pupa, Medrek, & Riordan, 2006). Engaging residents in activities might seem of less value for the wellbeing of residents, than the basic physical care, a clean environment and comfort (Clare et al, 2008;Edvardsson et al, 2013) À also the things by which the staff are often judged upon by family caregivers, colleagues and care facility.…”
Section: Introductionmentioning
confidence: 91%
“…One study looked at the implementation of a nursing guideline that emphasizes increasing pleasant activities and reducing negative events in several psychogeriatric nursing home wards, and found a significant decrease in depressive symptoms in residents with depression and dementia [75]. An examination of similar facilities in the Netherlands found that depressive symptoms in residents correlated with the level of social engagement on the unit, but this effect disappeared when individual resident characteristics (e.g., age, gender, level of function, presence of a partner) were taken into account [76].…”
Section: Clinical Managementmentioning
confidence: 99%
“…A study conducted by Verkaik et al . (,b) involved the introduction of nursing guidelines concerning depression in dementia and reported positive effects on the perceived professional autonomy of certified nursing assistants and a reduction in the severity of depression among residents with dementia. The idea of publishing nursing guidelines is promising, inviting future development and scientific evaluations that take into account both nurses and residents.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%